WORMS: CEPHALOPODS POLYCHACTES GEOHELMINTHS AND BIOHELMINTHS LEECHES IN MEDICINE - NIKHIL KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
The use of worms, cephalopods, polychaetes, geohelminths, biohelminths, and leeches in medicine has a long history, with these organisms being used for various medical purposes such as wound healing, bloodletting, and the treatment of certain diseases. In recent years, there has been renewed interest in studying the potential medical applications of these organisms. This research paper provides an overview of the different types of worms, cephalopods, polychaetes, geohelminths, biohelminths, and leeches used in medicine, as well as their potential therapeutic properties. Worms, cephalopods, polychaetes, geohelminths, biohelminths, and leeches have been used in medicine for centuries and continue to be studied for their potential medical applications. While some of these organisms have been found to have therapeutic properties, more research is needed to fully understand their potential benefits and limitations. Nevertheless, the use of these organisms in medicine represents an important area of research, with the potential to lead to new treatments and therapies for a variety of conditions. Therefore, further research and development are needed to unlock the full potential of these organisms for medical purposes.